Perbedaan aktivitas antimikroba dari ekstrak etanol dan etil asetat daun kopi (Coffea canephora) - Hartati Hartati; Suriati Eka Putri (Seminar Nasional LP2M UNM, 2019)
Coffee leaves have been widely used traditionally as herbal medicines by the community. Coffee leaves contain active compounds that are efficacious for treating various types of diseases. Some research results show that coffee has antibacterial activity because of the presence of various active compounds such as flavonoids, phenols, alkaloids and saponins. The use of coffee leaves is still low and research is rare compared to seeds. So it is very important to study coffee leaves more deeply. Extraction of the content of the active compound in the coffee leaf besides being influenced by the extract process or method is also strongly influenced by the type of solvent used. In this study 2 different types of solvents will be used, namely 70% ethanol as polar solvents and ethyl acetate solvents as non-polar solvents. Polar solvents will retract / attract polar compounds while non- polar solvents will dissolve non-polar compounds. In this study, the maceration method will be used in the extraction process using 70% ethanol and ethyl acetate. The results showed that coffee ethanol extract had high antibacterial activity and antifungal activity compared to coffee ethyl acetate extract.